2012
DOI: 10.1002/ange.201204274
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Direct CH Functionalization of Ethers: A Highly Efficient Approach to Chiral Spiroethers

Abstract: Spiroverbindungen: Eine organokatalytische asymmetrische C sp 3‐H‐Funktionalisierung racemischer cyclischer Ether in α‐Stellung gelingt in Gegenwart katalytischer Mengen eines Imidazolidinons und einer starken Säure. Der hoch enantioselektive Tandemprozess aus 1,5‐Hydridtransfer und Cyclisierung öffnet einen Zugang zu chiralen Spiroethern mit vielfältigen Strukturen (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…More recently, Tu and co‐workers successfully achieved the enantioselective 1,5‐hydride‐shift/cyclization reaction of racemic cyclic ethers 61 (Scheme ) 34. Impressive levels of diastereoselectivity were attained in this transformation.…”
Section: Enantioselective 15‐hydride‐shift Processesmentioning
confidence: 99%
“…More recently, Tu and co‐workers successfully achieved the enantioselective 1,5‐hydride‐shift/cyclization reaction of racemic cyclic ethers 61 (Scheme ) 34. Impressive levels of diastereoselectivity were attained in this transformation.…”
Section: Enantioselective 15‐hydride‐shift Processesmentioning
confidence: 99%
“…62%—87% yields, up to 94/6 dr and up to 96% ee (Scheme 1a). [ 5a ] In 2006, Yadav and co‐workers demonstrated that Lewis acid catalyzed [3+2] annulation of silylmethylcyclopropanes with cyclohexanone could provide a facile access to the racemic 1‐oxaspiro[4.5]decane (Scheme 1a). [6a] In 2012, Waser and co‐workers reported a catalytic enantiospecific [3+2] annulation of aminocyclopropanes with cyclohexanone, where enantioenriched cyclo‐…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In 2012, Tu and co‐workers reported a Macmillan catalyst 160 ‐catalyzed asymmetric α‐alkylation of tetrahydrofuran 158 containing an α,β‐unsaturated aldehyde to construct the chiral spiroether 159 (Scheme ) 52. The sequential [1,5]‐hydride transfer/cyclization was facilitated via a cascade iminium/enamine activation.…”
Section: C(sp3)h Bonds Adjacent To Ethereal Oxygenmentioning
confidence: 99%